On a Three-Step Iteration Process for Suzuki Mappings with Qualitative Study. (10th June 2020) - Maniu, Georgeta
Abstract: In this paper, we extend the study of an iteration process introduced by Thakur-Thakur-Postolache [ J. Inequal. Appl., (2014), 147–155] from the class of nonexpansive operators to the more general class of Suzuki operators. We prove weak and strong convergence theorems regarding the iteration method for mappings satisfying the condition (C) of Suzuki in uniformly convex Banach spaces. We study the stability of this iteration process, and introduce a data dependency result for the subclass of contractive operators. An example illustrates the theoretical outcome.